2022
DOI: 10.1155/2022/8285437
|View full text |Cite|
|
Sign up to set email alerts
|

Drug Resistance Mechanism of Enterobacteriaceae with Decreased Antibiotic Sensitivity

Abstract: To investigate the mechanism of antibiotic resistance in Enterobacteriaceae. Carbapenem Enterobacteriaceae bacteria isolated from a hospital from January 2015 to June 2020 were selected. Drug resistance phenotype test, drug sensitivity test, and conjugation test were used to observe the drug sensitivity results and the titer of acrB antibody. Finally, the data were statistically analyzed. All strains were resistant to ceftazidime, ceftriaxone, ertapenem, and aztreonam. 87.5% of the samples were resistant to pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This result is not different from that of Sanofi, which estimates that 30% of Klebsiella pneumoniae strains show resistance to 3rd generation cephalosporins in France, in 2020 [12]. Unlike Neisseria meningetidis, Enterobacteriaceae are widely distributed and have a large host range [24], they can cross-infect and spread between medical staff and patients, and also their genetic materials (such as plasmids or transposons) can be obtained from the outside world, leading to horizontal transmission of drug-resistant genes, which further leads to the wide spread of drug-resistant bacteria [25,26].…”
Section: Discussionmentioning
confidence: 60%
“…This result is not different from that of Sanofi, which estimates that 30% of Klebsiella pneumoniae strains show resistance to 3rd generation cephalosporins in France, in 2020 [12]. Unlike Neisseria meningetidis, Enterobacteriaceae are widely distributed and have a large host range [24], they can cross-infect and spread between medical staff and patients, and also their genetic materials (such as plasmids or transposons) can be obtained from the outside world, leading to horizontal transmission of drug-resistant genes, which further leads to the wide spread of drug-resistant bacteria [25,26].…”
Section: Discussionmentioning
confidence: 60%
“…This can lead to a reduction in the effectiveness of antibiotics against infectious pathogens. Furthermore, the irrational use of antibiotics has resulted in many pathogens developing multidrug resistance, which is a cause of great concern in the medical community [47]. In recent years, the widespread utilization of βlactamases has resulted in the elimination of the effectiveness of most cephalosporins against Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%